Assessing irritability in patients with stroke: psychometric properties of the Irritability Questionnaire. (2nd January 2020) - Mimentza, Naiara; González-Fraile, Eduardo; Arango-Lasprilla, Juan Carlos; Ortiz-Marqués, Nuria; Berrios, German E.; González-Pinto, Ana; Quemada, Jose I.
ABSTRACT: Objective : Irritability is a very common symptom after stroke and a source of a great deal of distress to patients and caretakers. We evaluated the psychometric properties of the Irritability Questionnaire (IQ) in a sample of patients with stroke. Methods : we recruited 94 participants (47 stroke patients and 47 healthy controls) that participated in a 6-month longitudinal observational study. The IQ includes three dimensions in the assessment: emotion, cognition, and behavior. IQ has two subscales: The Irritability Questionnaire (IRQ) and the Carer's Irritability Questionnaire (CIRQ). Internal consistency, convergent validity, and sensitivity to change were evaluated for both IRQ and CIRQ. Results : Cronbach's alpha for the IRQ was 0.91 (95% CI: 0.76 to 0.87), whereas for the CIRQ was 0.92 (95% CI: 0.89 to 0.94). Convergent validity was good for both subscales. IRQ did not show sensitivity to change at 6 months ( p -value = 0.99), while CIRQ showed moderate changes (−0.29, p -value = 0.124). Conclusions : IQ presented good psychometric properties to assess irritability in stroke. The tool detected significant differences between groups (stroke and healthy controls) and can be considered a valid instrument for clinical and research purposes.